Engaging the spirit world popular beliefs and practices in modern Southeast Asia - Endres, Kirsten W.; Lauser, Andrea (New York : Berghahn Books, 2012)
In many parts of the contemporary world, spirit beliefs and practices have taken on a pivotal role in addressing the discontinuities and uncertainties of modern life. The myriad ways in which devotees engage the spirit world show the tremendous creative potential of these practices and their innate adaptability to changing times and circumstances. Through in-depth anthropological case studies from Indonesia, Malaysia, Thailand, Myanmar, Laos, and Vietnam, the contributors to this book investigate the role and impact of different social, political, and economic dynamics in the reconfiguration o.
5: Gods, Gifts, Markets, and Superstition: Spirited Consumption from Korea to Vietnam6: Contests of Comm emoration: Virgin War Martyrs, State Memorials, and the Invocation of the Spirit World in Contemporary Vietnam; 7: Spirit Cults and Construction Sites: Trans-ethnic Popular Religion and Keramat Symbolism in Contemporary Malaysia; 8: Being a Spirit Medium in Contemporary Burma; 9: Reconfiguring Manora Rongkru: Ancestor Worship and Spirit Possession in Southern Thailand; 10: The Horror of the Modern: Violation, Violence, and Ramp aging Urban Youths in Contemporary Thai Ghost Films.
Includes bibliographical references and index.
Notes on ContributorsIndex.
Description based on print version record.
Keywords: Spiritualism -- Southeast Asia; Southeast Asia -- Religious life and customs; Religion and culture -- Southeast Asia; Popular culture -- Southeast Asia; Religion and culture -- Southeast Asia; Southeast Asia -- Religious life and customs; Spiritualism -- Southeast Asia; Philosophy; BODY, MIND & SPIRIT / Spiritualism; Electronic books